Fatores de risco para a infecção pelo vírus da leucose enzoótica bovina no sítio histórico e patrimônio cultural Kalunga - Peixoto, Sáudio Vieira (2016)
In the present study, the frequency of cattle infected by leukosis virus was evaluated in the herds of the Kalunga Historical Site and Cultural Heritage (SHPCK) and the association with environmental, sanitary and socioeconomic characteristics was performed. The SHPCK is located among the municipalities of Cavalcante, Monte Alegre de Goiás, and Teresina de Goiás, in the state of Goiás, 79 animals were included and blood samples were collected from 2,612 bulls (Curraleiro Pé-Duro and Caracu), zebu cattle (Nellore, Gir and Tabapuã) and crossbred animals. Detection of leukosis antiviral antibodies was performed using the agar gel immunodiffusion technique (IDGA - TECPAR ®). The edaphoclimatic variables of the municipalities were obtained through the database of the Laboratory of Image Processing and Geoprocessing (LAPIG) of UFG, at each point recorded in the GPS. Altitude data were collected from the Shutter Radar Topographic Mission satellite and zootechnical and socioeconomic data were obtained through questionnaires applied to the owners. The frequency of enzootic bovine leukosis in SHPCK herds was 29.29%. Among the different age groups, the following frequencies were observed: 12.8% at ages from 0 to 24 months, 32.1% from 25 to 36 months and 41.5% at ages over 36 months. The association between the studied variables and the frequency of leukosis showed a significant correlation for the breeds, age groups, vaccines, type of pasture available to cattle, family income, normalized difference vegetation index (INDV) and maximum temperatures in the warmer month.